Development of Ethnochemistry-Based E-Module on Corrosion Material to Accommodate Students' Critical Thinking Abilities - Aisah Aisah; Afrida Afrida; Aulia Sanova (Mathematics Education Study Program, 2025)
Technology significantly influences education. Emodules designed to be visually appealing, functional, and efficient, accessible on smartphones, laptops, or desktops, offer convenience for both educators and learners during the educational process. This research seeks to evaluate the development approach, practicality, efficiency, and effectiveness of emodules oriented towards ethnochemistry that focus on corrosion topics, aiming to enhance students' critical thinking abilities. The product development for this study adheres to the steps outlined in the Lee and Owens development framework. The research utilized interview forms and student needs assessment surveys as tools for gathering information. Data analysis included qualitative techniques for gathering suggestions and feedback, as well as quantitative methods for evaluating scores. Findings from the study indicated that the ethnochemistrybased emodules were both conceptually and procedurally viable, as determined by evaluations from material and media specialists, achieving average scores of 4. 94 and 4. 53, categorizing them as very feasible. Feedback from chemistry educators resulted in a favorable percentage of 92. 22% (very feasible), alongside positive student reactions reflected in a 93. 2% approval rating. Furthermore, the assessment of critical thinking skills revealed a 70% satisfaction level, indicating favorable responses to the emodule from students. In conclusion, the research findings suggest that the developed emodule focused on corrosion and based on ethnochemistry is both valid and suitable for educational use, supported by positive student feedback.